2018
DOI: 10.1007/s11748-018-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Leaflet escape in an Edwards TEKNA mitral prosthesis

Abstract: In almost every type of artificial valve, structural failure has been described. We are reporting on a case of a sudden leaflet escape of an Edwards TEKNA mitral valve prosthesis 12 years after implantation. The patient had a sudden onset of dyspnea and severe pulmonary edema with subsequent cardiogenic shock. An emergency mitral replacement was successfully performed. A multi-detector computed tomography scanning and three-dimensional imaging showed two fragments that had embolized in the terminal aorta and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Nakamura et al reported cases in which the escape leaflets (leaflet rupture) were surgically removed in time, but the author only reported the cases and did not report on the mid-term and long-term follow-up results. Some published researches in the literature recommend removing the escaped leaflet within the short period of replacing the dysfunctional heart valve in stable conditions [16][17][18][19]. Therefore, the advantages and disadvantages of the two treatment schemes can be selected according to a case by case basis, without more evidence-based guidelines.…”
Section: Treatment Strategy Of Leaflet Escapementioning
confidence: 99%
“…Nakamura et al reported cases in which the escape leaflets (leaflet rupture) were surgically removed in time, but the author only reported the cases and did not report on the mid-term and long-term follow-up results. Some published researches in the literature recommend removing the escaped leaflet within the short period of replacing the dysfunctional heart valve in stable conditions [16][17][18][19]. Therefore, the advantages and disadvantages of the two treatment schemes can be selected according to a case by case basis, without more evidence-based guidelines.…”
Section: Treatment Strategy Of Leaflet Escapementioning
confidence: 99%